(untitled) (Palestine Technical College Journal for Research and Studies, 2022)
This study aimed to demonstrate the impact of corporate governance in its various dimensions (participation, evaluation, accountability, effectiveness, transparency, justice and equality) on improving the financial performance of the Gaza Governorate Electricity Distribution Company, as well as studying the relationship between institutional governance in its various dimensions and improving financial performance. Where the study used the descriptive analytical approach and a questionnaire was designed to collect data related to the study variables, and 306 questionnaires were distributed to the study sample according to job titles (department manager, department head, division head, administrator) in the Gaza Electricity Distribution Company, and after completing the data collection process; The outcome of the collection reached 267 questionnaires, with a recovery rate of 87.25%. The study reached several results, including the presence of a positive direct correlation between the application of corporate governance in its various dimensions (participation, evaluation, accountability, effectiveness, transparency, justice and equality) and improving the efficiency of financial performance. There is also an impact of the application of corporate governance in its various dimensions on improving the efficiency of financial performance in the company. Based on the results of the study; The study researcher reached several recommendations, including: raising the level of interest in institutional governance and its practice within the company, and increasing the activation of accountability at all administrative levels without discrimination; While enhancing transparency among employees, reviewing regulations and laws to increase justice and equality, and working to enhance the aspect of job satisfaction and institutional affiliation when setting administrative policies.